Mitochondrial Damage-Associated Molecular Patterns of Injured Axons Induce Outgrowth of Schwann Cell Processes - Korimová, Andrea; Klusáková, Ilona; Hradilová-Svíženská, Ivana; Kohoutková, Marcela; Joukal, Marek; Dubový, Petr (Frontiers in Cellular Neuroscience, 2018)
Activated Schwann cells put out cytoplasmic processes that play a significant role in cell migration and axon regeneration. Following nerve injury, axonal mitochondria release mitochondrial damage-associated molecular patterns (mtDAMPs), including formylated peptides and mitochondrial DNA (mtDNA). We hypothesize that mtDAMPs released from disintegrated axonal mitochondria may stimulate Schwann cells to put out cytoplasmic processes. We investigated RT4-D6P2T schwannoma cells (RT4) in vitro treated with N-formyl-L-methionyl-L-leucyl-phenylalanine (fMLP) or cytosine-phospho-guanine oligodeoxynucleotide (CpG ODN) for 1, 6 and 24 h. We also used immunohistochemical detection to monitor the expression of formylpeptide receptor 2 (FPR2) and toll-like receptor 9 (TLR9), the canonical receptors for formylated peptides and mtDNA, in RT4 cells and Schwann cells distal to nerve injury. RT4 cells treated with fMLP put out a significantly higher number of cytoplasmic processes compared to control cells. Preincubation with PBP10, a selective inhibitor of FPR2 resulted in a significant reduction of cytoplasmic process outgrowth. A significantly higher number of cytoplasmic processes was also found after treatment with CpG ODN compared to control cells. Pretreatment with inhibitory ODN (INH ODN) resulted in a reduced number of cytoplasmic processes after subsequent treatment with CpG ODN only at 6 h, but 1 and 24 h treatment with CpG ODN demonstrated an additive effect of INH ODN on the development of cytoplasmic processes. Immunohistochemistry and western blot detected increased levels of tyrosine-phosphorylated paxillin in RT4 cells associated with cytoplasmic process outgrowth after fMLP or CpG ODN treatment. We found increased immunofluorescence of FPR2 and TLR9 in RT4 cells treated with fMLP or CpG ODN as well as in activated Schwann cells distal to the nerve injury. In addition, activated Schwann cells displayed FPR2 and TLR9 immunostaining close to GAP43-immunopositive regenerated axons and their growth cones after nerve crush. Increased FPR2 and TLR9 immunoreaction was associated with activation of p38 and NFkB, respectively. Surprisingly, the growth cones displayed also FPR2 and TLR9 immunostaining. These results present the first evidence that potential mtDAMPs may play a key role in the induction of Schwann cell processes. This reaction of Schwann cells can be mediated via FPR2 and TLR9 that are canonical receptors for formylated peptides and mtDNA. The possible role for FPR2 and TLR9 in growth cones is also discussed.